1995
DOI: 10.1111/j.1745-6584.1995.tb00321.x
|View full text |Cite
|
Sign up to set email alerts
|

Virus and Bacteria Transport in a Sandy Aquifer, Cape Cod, MA

Abstract: Transport of the bacteriophage PRD‐1, bacteria, and latex microspheres was studied in a sandy aquifer under natural‐gradient conditions. The field injection was carried out at the U.S. Geological Survey's Toxic Substances Hydrology research site on Cape Cod. The three colloids and a salt tracer (Br−) moved along the same path. There was significant attenuation of the phage, with PRD‐1 peak concentrations less than 0.001 percent of Br− peaks 6 m from the source; but the low detection limit (one per ml) enabled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(76 citation statements)
references
References 16 publications
4
72
0
Order By: Relevance
“…Harvey and Garabedian [51] applied filtration theory to quantitatively model transport of bacteria in a subsequent naturalgradient experiment at the same site, and estimated a collision efficiency of 5 Â 10 À3 to 1 Â 10 À2 at a travel distance of 6.9 m. Harvey et al [52] demonstrated the importance of physical heterogeneity in controlling field-scale bacterial transport. Observations of micro-sphere, bromide, and bacterial transport 6 m downgradient of the injection point varied significantly in three sampling ports separated by a total vertical distance of 0.7 m. Bales et al [5] observed bacterial breakthrough at a distance of 11 m, but their experiment focused on effects of pH on phage (virus) attenuation and remobilization. Harvey et al [53] studied the transport of groundwater protozoa at the Cape Cod site, and found that the protozoa were attenuated more rapidly than bacteria although the protozoa were of the optimal size for transport based on experiments with microspheres of various diameters.…”
Section: Previous Field-scale Bacterial Transport Experimentsmentioning
confidence: 99%
“…Harvey and Garabedian [51] applied filtration theory to quantitatively model transport of bacteria in a subsequent naturalgradient experiment at the same site, and estimated a collision efficiency of 5 Â 10 À3 to 1 Â 10 À2 at a travel distance of 6.9 m. Harvey et al [52] demonstrated the importance of physical heterogeneity in controlling field-scale bacterial transport. Observations of micro-sphere, bromide, and bacterial transport 6 m downgradient of the injection point varied significantly in three sampling ports separated by a total vertical distance of 0.7 m. Bales et al [5] observed bacterial breakthrough at a distance of 11 m, but their experiment focused on effects of pH on phage (virus) attenuation and remobilization. Harvey et al [53] studied the transport of groundwater protozoa at the Cape Cod site, and found that the protozoa were attenuated more rapidly than bacteria although the protozoa were of the optimal size for transport based on experiments with microspheres of various diameters.…”
Section: Previous Field-scale Bacterial Transport Experimentsmentioning
confidence: 99%
“…It is often more difficult to measure viral and bacterial abundance in porous media such as soils and sediments than in water samples due to the necessity of removing viruses and bacteria from the sediment matrix. Although a priori studies have shown the effects of clay (33,35), pH (3,31), and organic matter (42,56) on viral mobility and transport, none have addressed extractability. Correlation For Chesapeake Bay sediments, correlation analysis showed that the sand and clay composition had the most significant correlations to viral abundances (P Ͻ 0.01), with lesser contributions from porosity and water content (P Ͻ 0.05).…”
Section: Fresh or Frozenmentioning
confidence: 99%
“…Labeling cells with fluorescent stains has been employed to examine bacterial attachment to surfaces (13), to count the numbers of total and active cells in a variety of environmental samples (37,39,55), and for in situ injection of groundwater bacteria (1,(16)(17)(18)(19). One of the stains used, 4Ј,6-diamino-2-phenylindole (DAPI), specifically binds to nucleic acids (RNA and DNA), which enables it to universally label cells in an organism-independent manner.…”
mentioning
confidence: 99%